Chemical Synthesis and Characterization of γ-Co2NiGa Nanoparticles with a Very High Curie Temperature - Wang, Changhai; Levin, Aleksandr A.; Nasi, Lucia; Fabbrici, Simone; Qian, Jinfeng; Barbosa, Carlos E. Viol; Ouardi, Siham; Karel, Julie; Albertini, Franca; Borrmann, Horst; Fecher, Gerhard H.; Felser, Claudia (Chemistry of Materials, 2015)
We report the first study on the chemical preparation, structural characterization, and magnetic properties of Co2NiGa nanoparticles (NPs) of a single γ-phase (γ-Co2NiGa). The γ-Co2NiGa NPs were prepared by impregnation in colloidal silica followed by high temperature annealing under hydrogen atmosphere. The crystal structure of tetragonal γ-Co2NiGa was confirmed by selected area electron and X-ray diffraction studies. Energy-dispersive X-ray spectroscopy mapping and X-ray absorption near edge structure data provided evidence for the successful preparation of the intermetallic NPs and the absence of Co, Ni, Co-Ni, or metal-containing impurity phases. Extended X-ray absorption fine structure spectroscopy data confirmed the formation of the γ-Co2NiGa phase by examining the atomic environments surrounding Co, Ni, and Ga. The Co2NiGa NPs are ferromagnetic with a high saturation magnetization, which is consistent with the theoretical model. γ-Co2NiGa NPs exhibit a very high Curie temperature (≈1139 K), which make them promising candidates for high temperature magnetically activated nanoscale devices.
CRIS-Team Scopus Importer:2023-03-20